Volumetric modulated arc therapy applied to synchronous bilateral breast cancer radiotherapy: dosimetric study on deep inspiration breath hold versus free breathing set up. (11th May 2018) - Gaudino, D; Cima, S; Frapolli, M; Daniele, D; Muoio, B; Pesce, GA; Martucci, F; Azinwi, NC; Bosetti, D; Bellesi, L; Casiraghi, M; Piliero, MA; et al.
Abstract: Aim . The purpose of this planning report is to compare dosimetric results of deep inspiration breath hold (DIBH) and free breathing (FB) set up in patients with synchronous bilateral breast cancer (SBBC) treated with adjuvant radiotherapy. Material and methods . Fourteen patients with early stage bilateral breast cancer were treated with breast conservative surgery. Bilateral breast planning treatment volume (PTV) and organs at risk (OARs) were delineated for DIBH and FB datasets on the planning computed tomography (CT). Volumetric modulated arc therapy (VMAT/RapidArc ®) plans were generated in the two set up modalities. During plan optimization the objectives were to obtain comparable target coverage, dose conformity and homogeneity with an acceptable dose levels for OARs: both lungs, heart, left anterior descending coronary artery (LAD) and thyroid. Results . The maximum and the mean dose to the heart were reduced in DIBH modality with an average of 19.2 Gy and 6.5 Gy versus 25.9 Gy and 8 Gy in FB. The mean dose to the sum of lungs was 13.3 Gy in DIBH modality versus 14.3 Gy in FB. We observed a better sparing of LAD in DIBH with a maximum dose of 14.5 Gy versus 18 Gy in FB modality. Conclusions . DIBH allows a better sparing of heart and LAD compared to FB modality; it provides better results in term of mean dose to the sum of lungs. The clinical impact on acute and late toxicity is under investigation.